Do Gender, Child, and Parent Characteristics Contribute to Intergenerational Subjective Well-being Mobility? Evidence from Russia during 1994-2019 - Hai-Anh H. Dang; Kseniya Abanokova (Global Labor Organization (GLO), 2022)
Measuring the intergenerational mobility of welfare provides key inputs for policies, but very few studies examine intergenerational mobility of subjective well-being (SWB), particularly in a poorer, transitional country context. We make new contributions by analyzing rich panel SWB data from Russia over the past quarter century, which address various shortcomings with traditional income data. We find that intergenerational SWB mobility-as measured by subjective wealth and life satisfaction-exists, with daughters having higher transmission of SWB from their mothers than sons. Adding other child and parent characteristics to the multivariate regression models can reduce the estimated impacts of mothers' SWB by up to 40% but does not change the gender gaps in the intergenerational transmission. Our results are robust to different model specifications and sample restrictions.
Keywords: D6; I3; J6; O1; 330; intergenerational mobility; life satisfaction; subjective wealth; gender; panel data; Russia